Facile fabrication of Zn0.6Cd0.4S/ZnO/g-C3N4 dual Z-scheme heterostructures with enhanced performance under visible light: an experimental and theoretical study - Yuqi Dong; Qing-an Qiao; Ruping Wang; Yueyue Yang; Honglan Cai; Hongwei Gao (Scientific Reports)
Abstract Environmental pollution caused by industrial waste is an increasing concern, and the design and development of efficient photocatalysts offer promising approaches to address this issue. A series of novel Zn0.6Cd0.4S/ZnO/g-C3N4 composites were prepared through a calcination‒hydrothermal method. Under visible light, these materials demonstrated exceptional performance in the photodegradation of methylene blue (MB), rhodamine B (RhB), and tetracycline (TC). Among the composite materials, Z0.6C0.4S/ZnO/CN-35% exhibited the highest degradation efficiencies for MB (98.52%), RhB (99.45%), and TC (98.20%), demonstrating excellent reusability as well. The photocatalytic performance of the catalysts was assessed across various water sources and different pH conditions. The findings revealed that the degradation efficiency for contaminants in seawater, lake water, and tap water closely mirrored that observed in deionized water, suggesting wide adaptability among different aqueous solutions. The exceptional photocatalytic performance of the composite materials can be attributed primarily to the efficient separation and migration of holes (h+) and electrons (e−) via well-contacted interfaces. Free radical capture experiments confirmed that hydroxyl radicals (·OH) and superoxide ion radicals (·O2 -) play crucial roles in the reaction process. The photocatalytic mechanism was also revealed via density functional theory (DFT) calculations. This work introduced an innovative strategy to design and fabricate novel photocatalysts, emphasizing their extensive applications from both theoretical and experimental aspects.